Remembering stories together: Social contagion and the moderating influence of disagreements in conversations - Muller, Felipe Juan (2013)
Although remembering often occurs with conversations, the effects of its pragmatics on memory are rarely examined. We studied the effect of two pragmatic factors: (1) the presence of disagreeing and (2) the level of participation in the disagreement. In the present study, each participant read a slightly different version of four stories, thereby allowing for the possibility of social contagion through the conversation. They then jointly recounted the stories. We coded for the presence or absence of disagreements, and whether a participant contributed to the disagreement. Three factors mediated social contagion: (a) the presence or absence of an overt disagreement; (b) whether or not a member of a conversational remembering participated actively in a disagreement; and (c) how well participants remembered the original material. Both the pragmatics of conversations and quality of memory are important factors moderating social contagion.